Nipple-sparing mastectomy in normal breast: consequence of simulation and disease anxiety - Soares, Leonardo Ribeiro; Teixeira-Silva, Savio Augusto; Caetano, Murilo Ferreira; Modesto, Gustavo Amaral; Moreira, Marise Amaral Rebouças; Freitas-Junior, Ruffo (Mastology, 2021)
Diagnosis in psychiatry is a thorough and potentially artificial process. In this letter, we discuss this diagnostic process in the context of a young patient who underwent nipple-sparing mastectomy after falsifying a breast biopsy report revealing invasive ductal carcinoma. The secondary pathology revision was also forged by the patient and confirmed the diagnosis. The patient was summoned by the Service’s board and admitted the falsification of breast cancer reports. After evaluation at the Psychiatric Service, changes in vital mood, psychosis, delusional activity and obsessive-compulsive symptoms were ruled out. In view of the growing demand for prophylactic mastectomy observed worldwide, similar cases may become more frequent.